Activity and dust environment of comet 67P/Churyumov-Gerasimenko - Zaprudin, Boris (fi=Turun yliopisto|en=University of Turku|, 2018)
Comets are scientifically interesting objects for several reasons. Comets are among the most pristine objects of the Solar System, which can give us a way to directly study the imprints of the Solar System formation processes. Comets may have been the main mechanism for delivering volatile compounds, such as water, into the inner Solar System, including the Earth. In addition, comets contain a fair amount of complex organic material which may have descended on the primordial Earth and contributed to the emergence of life. Ground-based observations of comets have limited capabilities. Therefore, cometary space missions were designed and performed during the last few decades. The most recent and elaborated one was the Rosetta mission, performed by the European Space Agency. This mission has provided us with a unique set of in-situ data, making comet 67P/C-G one of the most studied minor bodies of the Solar System. However, space missions are limited in number and by the types of objects they can reach, resulting in only few comets that were studied in-situ. It is, thus, extremely important to transfer the knowledge gained through the space missions to other comets which have only been observed from the ground. In this work, an introductory review of the subject as well as four original research articles are presented. Two articles cover the activity and coma structure evolution of comet 67P/C-G during the Rosetta mission, monitored with the Nordic Optical Telescope. The other two articles present the in-situ data obtained with the COSIMA instrument onboard Rosetta and the analysis tools developed for the instrument. The activity of comet 67P/C-G is studied on several scales: from the individual microscopic dust particles, collected by COSIMA in the proximity of the comet’s nucleus, to the global structures of the coma, reaching 104 kilometers, observed from the ground. These methods are complementary: the local data obtained by Rosetta are unresolvable for the ground-based telescopes, while remotely observed coma structures are not visible to Rosetta’s instrumentation.